Validation of Si-HIPO mHealth application for hypertension-obesity education in Surakarta - Sunarsih Rahayu; Ros Endah Happy Patriyani (Intelektual Pustaka Media Utama, 2026)
Hypertension and obesity represent significant global public health challenges requiring innovative educational interventions. The Si-hypertension and obesity information system (HIPO) application was developed as a context-specific digital health education medium targeting Indonesian community health center populations, distinguishing it from existing generic mHealth tools by integrating comorbid hypertension-obesity education within a culturally appropriate single platform. This study aimed to assess the content validity of the Si-HIPO application through expert and respondent validation. A quantitative descriptive cross-sectional design was employed at Sibela Community Health Center, Surakarta, Indonesia. Expert validation involved two assessors using Aiken's V coefficient methodology, while respondent validation included 66 participants with hypertension and overweight/obesity. Respondent characteristics revealed predominantly female participants (60.61%), aged > 40 years (39.39%), with stage 2 hypertension (51.52%) and obesity (59.09%). Respondent evaluation demonstrated 72.73% positive acceptance. Expert validation yielded high validity coefficients for nine of ten items (V = 0.802-0.833), with one item showing moderate validity (V = 0.667). The aggregated validity coefficient was 0.802, indicating high overall content validity. The Si-HIPO application demonstrates strong content validity and user acceptability as an educational medium for hypertension and obesity management. However, further effectiveness testing through experimental or quasi-experimental designs is warranted before implementation in clinical practice.